Assessing the Potential of “Mobility as a Service” in Passenger Maritime Transport - Papaioannou, Georgios; Polydoropoulou, Amalia; Tsirimpa, Athena; Pagoni, Ioanna (Frontiers in Future Transportation, 2022)
This paper assesses the potential of Mobility as a Service in Passenger Maritime Transport from the supply perspective by collecting and analyzing data of key experts in passenger transport both from industry and academia. “Mobility as a Service” in Passenger Maritime Transport (also in this paper referred as “Maritime MaaS”) includes the integration of passenger maritime services with land mobility into a single mobility service delivered through a unique platform for planning, booking, ticketing and payment. The scope of this paper is to explore the potential interest of mobility service providers to develop a MaaS that has as a backbone coastal shipping at the Aegean Archipelagos, in Greece. The maritime MaaS ecosystem with its key actors is identified, while the perceived challenges, opportunities and benefits envisaged by the adaptation of this innovative concept from urban transport to the maritime sector are recorded. Computer assisted interviews (CAI) were performed at a panel of 17 experts representing different types of decision makers. Participants were selected according to their current industry position or their academic profile. A content analysis with the use of NVIVO was conducted, followed by a SWOT analysis based on the experts’ input, in order to assess the MaaS business environment. Results indicate that the maritime transport sector is relatively ready to adopt MaaS from a technological readiness perspective, whilst land transport seems to be in a lower level of technological readiness. Pay as you go (PAYG) MaaS business model is preferred than a “MaaS package” model by most stakeholders. Finally, main challenges towards Maas implementation are the discrepancies in reliability of service among different transport modes and the ferry fleet operational flexibility ceilings that are imposed by legal framework for ferry routings in Greece.